The Impact of COVID-19 on Mental Health and Healthcare in Youth with Chronic Physical Illness and Their Families - Reese Parks; Chloe Bedard; Jennifer Yessis; Samantha B. Meyer; Mark A. Ferro (Psychiatry International)
The COVID-19 pandemic disproportionately impacted youth with chronic physical illness (CPI) and their caregivers. Emerging research aimed at understanding the impacts of the pandemic on this population is predominantly quantitative, lacking qualitative insights. This study used a qualitative approach to examine the experiences of COVID-19 among youth with CPI and their families, exploring how the pandemic impacted their mental health and use of mental health services. Using a constructivist paradigm and a phenomenological approach, semi-structured interviews were conducted with youth with CPI (n = 8) and their primary caregiver (n = 13) between March 2021 and May 2021. Thematic analysis was used to identify three key themes: (1) mental health impact on youth, (2) caregiver mental health declines, and (3) variability in the experiences of mental healthcare. The findings highlight the heightened depression, anxiety, and stress among youth with CPI and their caregivers, exacerbated by loneliness, uncertainty, and social restrictions, while also revealing that virtual mental healthcare was perceived as less effective than in-person care, which was valued for its human connection, privacy, and comfort. These results emphasize the need for improved, comprehensive mental healthcare and the adoption of family-centred care models to strengthen caregiver–youth relationships and better integrate physical and mental healthcare to improve health outcomes for this population.